Pengaruh Motivasi Belajar terhadap Prestasi Belajar PAI di MIN 3 Bantul - Noor Biatun (Jurnal Pendidikan Madrasah, 2020)
This research aims to find out the level of motivation of students and the influence of motivation on PAI learning achievement in schools on MIN 3 Bantul students. This research is a quantitative study using product moment correlation statistics technique. The analytical technique used is an associative hypothesis. The variables studied include learning motivations that are divided into sub variables namely personal needs, school assignments, as well as the environment and people around. While dependent variables (bound variables) are learning achievements that include: academic achievement, non-academic achievement, social achievement and discipline-related achievements. The results showed that learning motivation affects PAI students' learning achievement of MIN 3 Bantul by 51.4%. This means that learning motivation is one of the determining factors of PAI's learning achievements. While 48.6% of PAI students' learning achievement of MIN 3 Bantul students is influenced by internal factors such as IQ, perseverance; and external factors such as family issues, friendships etc.). This indicates that motivation is both a driver and a direction in learning activities.